Theory of Virus Public Infection Through The Weiss Approach - Nieto-Chaupis, Huber (2020)
A theory of virus infection in humans by using the Weiss’s approach is presented. For this end it was associated physical observables such as the distance and wind velocity. The model assumes random quantities from the fact that the confluence of healthy and infected people has not any known law. In this manner we adjudicate various probabilities that might to encompass a realistic scenario. From the resulting theoretical model, various curves of probability and infections have demonstrated that still under a scheme of care outdoor, the wind velocity can be a important factor of infections in open areas. In this manner, a single infected can transmit the strain in a radius of 5 for a wind velocity of 7m/s.